PENGARUH REPUTASI PERUSAHAAN TERHADAP LOYALITAS NASABAH PADA JASA ASURANSI (KASUS PADA PT.ASURANSI BSAM CABANG PEKANBARU) - Utari, Desi Suci; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study aimed to determine the effect of the Corporate Reputation on Customer Loyalty of PT Insurance BSAM branch Pekanbaru.corporate reputation as an independent variable (X).while costumer loyality as the dependent variable (Y). study was conducted on customer Non Captive in PT.Insurance BSAM Branch Pekanbaru by 99 people.Data obtained from the questionnaire and further processed and tested using statistical analysis such as simple regression analysis , t test, correlation analysis and determination using SPSS program.The results showed that the test results of hypothesis testing. tcount(22.558) >ttable (1.66071). This suggest that the corporate reputation affect the costumer loyality. The magnitude of the corporate reputation on costumer loyality in PT.Insurance BSAM Branch Pekanbaru is 84%.Keyword:the company reputation and costumer loyality